FXIII: mechanisms of action in the treatment of hemophilia A. (February 2014) - Rea, C. J.; Foley, J. H.; Okaisabor, O.; Sørensen, B.
Summary Background Hemophilia is characterized by abnormal thrombin generation and impaired clot stability. FXIII promotes clot stability and may be a useful adjunct treatment for hemophilia. Objectives This study examined the clot stabilizing effects and safety of supra‐physiological FXIII and explored the mechanisms via which FXIII exerts its effects in hemophilia A. Methods The effects of FXIII on clot formation and stability were examined using a thromboelastometry assay and blood samples collected from six patients with severe hemophilia A. The effect of FXIII on clot formation was also assessed using a murine model. The mechanisms of FXIII action in hemophilia A were explored by measuring thrombin generation, rates of FXIII activation and effects on clot permeability, pore size and fibrin fiber diameter. Results This study demonstrates that supra‐physiological concentrations of FXIII stabilize clots in blood from patients with hemophilia by improving resistance to t‐Pa‐induced fibrinolysis even at low concentrations of FVIII (FVIII< 0.1 IU mL−1, P < 0.05, anova). Addition of FXIII stoichiometrically up‐regulates its activation, correcting the fibrin clot structure, reducing clot permeability and facilitating thrombin generation; FXIII significantly shortens ttPeak and lagtime (P < 0.05) in FVIII‐deficient plasma, providing a novel explanation for its positive effects on clot stability and structure. The murine model indicates that supra‐physiological FXIII is tolerated and does not significantly alter time to clot formation. Conclusion The effects of FXIII on clot stability and physical clot structure are seen at low concentrations of FVIII, indicating that FXIII could be a useful treatment in a variety of clinical scenarios.